A SYSTEMATIC LITERATURE REVIEW OF CRISIS MANAGEMENT - Didik Widiantoro; Md Azman Shahadan (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The rising frequency and complexity of crises in various sectors underscore the critical need for robust crisis management frameworks. This study conducts a systematic literature review (SLR) to synthesize the diverse perspectives and strategies within the field of crisis management, aiming to provide a comprehensive understanding of current trends and emerging challenges. The review adheres to the PRISMA guidelines, utilizing databases such as Google Scholar, ProQuest, and ScienceDirect to identify relevant literature. An initial search yielded approximately 603,327 publications related to "crisis management." Given the vast scope of this field, selection criteria were applied to refine the results, focusing on the most relevant studies. The literature reveals significant themes, including the evolving role of leadership, the integration of technology, and the importance of organizational agility in managing crises. The findings highlight the need for continuous adaptation and innovation in crisis management strategies to address the challenges posed by globalization, technological advancements, and climate change. , ,